Evaluating Mental Health Disability in the Workplace Model, Process, and Analysis - Gold, Liza; Shuman, Daniel W. (Springer New York : Imprint: Springer, 2009)
As many as one in four adults in the workforce will suffer from psychiatric illness in a given year. Such illness can have serious consequences -- job loss, lawsuits, workplace violence-yet the effects of mental health issues on job functioning are rarely covered in clinical training. In addition, clinicians are often asked to provide opinions on an employee's fitness for work or an evaluation for disability benefits, only to find themselves embroiled in complex legal and administrative conflicts. A unique collaboration between a renowned clinical professor of psychiatry and a noted legal expert, Evaluating Mental Health Disability in the Workplace approaches the topic from two distinct areas: the legal context and issues relevant to disability and disability-related evaluations, and the interplay of factors in the relationship between work and psychiatric illness. From this dual perspective, the authors advocate for higher professional standards ensuring that employers, evaluees, or third parties are provided with the most reliable information. Key features of the book: A robust assessment model of psychological disability in the workplace Practice guidelines for conducting workplace mental health disability evaluations Legal and ethical aspects of employment evaluations, especially as they differ from clinical procedure Examination of the process of the development of psychiatric disability Issues specific to evaluations for Social Security, Workers' Compensation, and other disability benefit programs Issues specific to evaluations for the Americans with Disabilities Act and Fitness-For-Duty evaluations Review of relevant administrative and case law As an introduction to these complex issues or for the further improvement of evaluation skills, Evaluating Mental Health Disability in the Workplace is a timely reference for psychiatrists, psychologists, forensic mental health specialists, and attorneys in this field.